Study on Different Range of NIR Sensor Measurement for Different Concentration of Glucose Solution - Mohd Saad, W.H.; Abd Salam, N.A.; Salehuddin, F.; Azmi Ali, M.H.; Abd. Karim, S.A. (International Journal of Human and Technology Interaction (IJHaTI), 2017)
The development of noninvasive methods to replace the conventional finger pricking method to measure the blood glucose concentration is developing rapidly. This study was conducted to evaluate different wavelength of near infrared (NIR) sensors that is going to be the best in measuring the glucose concentration samples that was prepared. Three different wavelengths of NIR sensor are used for the testing, 800 nm, 940 nm and 950 nm. Several experiments were conducted to find the relationship between the output voltages and glucose concentration. The results of the experiments proved that the linear relationship between output voltages and glucose concentration is significant for all NIR sensors used and the NIR sensor with a wavelength of 940 nm shows the best fit.